Effects of Contraction Joints on Vibrational Characteristics of Arch Dams: Experimental Study - S. S. Wang; Y. F. Zhang; M. S. Cao; W. Xu (Shock and Vibration)
This study experimentally investigates the effects of contraction joints on the vibrational characteristics of high arch dams. Three scale models of the world’s second highest dam, the Xiaowan Arch Dam, are used as experimental specimens identified by zero, one, and two contraction joints. When a scale model vibrates harmonically at a specific frequency, its operating deflection shape is acquired by using a scanning laser vibrometer to scan the side surface of the model. The effects of contraction joints on the vibrational characteristics of arch dams are studied by examining the changes in operating deflection shapes. Experimental results demonstrate that (i) contraction joints can significantly affect the vibrational characteristics of arch dams, (ii) the operating deflection shape intuitively illustrates the vibrational characteristics of arch dams, and (iii) a scanning laser vibrometer has marked advantages over traditional equipment in accurately and efficiently acquiring full-field dynamic responses of a structure.